Toning the sweep - Johnson, Angela, 1961- (New York : Orchard Books, 1993)
On a visit to her grandmother Ola, who is dying of cancer in her house in the desert, fourteen-year-old Emmie hears many stories about the past and her family history and comes to a better understanding of relatives both dead and living.
"A Richard Jackson book"--Half title p.
Keywords: Grandmothers -- Fiction; Family life -- Fiction; Deserts -- Fiction; Cancer -- Fiction; African Americans -- Fiction